Agricultural Insurance with State Support in Russia in the Conditions of Uncertainty and Risk - Konstantinovna Ulibina, Lubov; Alekseevna Okorokova, Olga; Borisovich Turaev, Yuri; Antsasovna Rusetskaya, Elvira; Vladimirovna Il'ina, Tatiana (International Journal of Engineering and Technology, 2018)
The relevance of the topic of the research is determined by the necessity to implement insurance as a method to control agricultural risks in order to increase the financial stability of agricultural producers in the conditions of high uncertainty of natural and climatic conditions.Insurance as a means to stabilising risks in the agrarian sphere enables not only to compensate for the losses connected with the loss of agricultural products but also to protect the producers from possible bankruptcy, to enhance the predictability of financial outcomes of activities. The authors put the greater emphasis on the underlying factors influencing the formation and dynamics of crucial indicators of agricultural insurance with state support compared to Russian and foreign experience. The sectoral analysis of was carried out, the peculiarities of implementing instruments of agricultural insurance in terms of federal districts and insurance institutions were revealed, provisions on innovative programmes were developed in order to improve agreements between actors for strengthening agricultural producersâ€™ activities.Â Â